Features Of The Functioning Of The External Respiratory System In Children In The Conditions Of The Southern Near Aral Sea - Nadira Mirametova,; Gulayim Serekeeva,; Gulnaz Begdullaeva,; Gulchehra Kudeshova,; Gaukhar Dosjanova, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The unique ecological and climatic features of the southern Near Aral Sea region have a great impact on the respiratory health condition of its inhabitants, especially children. The ecological changes caused by the desiccation of the Aral Sea have led to severe environmental degradation, which increased salinity, dust, and release of harmful pollutants into the air. These factors present a big threat to children's respiratory health in view of their greater vulnerability to environmental hazards. This study will, therefore, analyze the functioning of the external respiratory system in children living in this region. It adopts a mixed-methods approach: clinical observation, spirometry testing, and environmental monitoring to give a comprehensive understanding of the situation. Clinical observations look for symptoms such as shortness of breath, chronic cough, and wheezing. Spirometry testing offers quantitative data on lung function, while environmental monitoring measures key indicators like air quality, salinity, and dust concentration. Together, these methods provide a holistic view of how environmental factors affect respiratory health. The results indicate large-scale departures from the national averages of respiratory functions among children in the area. These included lower lung volumes, impairment of respiratory flow, and increased prevalence of respiratory symptoms. High salinity, air pollution, and fine particulate matter from salt and dust storms are identified as major contributors. This factor's effect is more pronounced in younger children due to the developing respiratory system being more prone to the injurious effects of environmental pollutants. The discussion, therefore, really underlines the urgent need for targeted health interventions in the form of environmental remediation, better air quality monitoring, and development of healthcare programs that will address the particular needs of children in the region. Protection of respiratory health in environmentally challenged areas, like the Near Aral Sea region, needs coordination among health authorities, environmental agencies, and community stakeholders.